Addressing the Factors Influencing Customer Satisfaction of 3G Mobile Phone Services: A Case of Dhaka City, Bangladesh (Global Journal of Management and Business Research, 2016)
Now a day#x2019;s 3G mobile phone services are very essential to the telecommunication organizations to attract their customers. To provide better service, it is also necessary for these organizations to know customer satisfaction factors of 3G service. Therefore this study has been conducted to address the factors that will influence satisfaction of customer toward these services in Dhaka city. Seventeen potential customer satisfaction influencing factors are taken into consideration in this study. Data has been collected from both primary and secondary sources. Multiple regression and factor analysis have been conducted on the primarily collected data. The outcome of this paper is that network quality, price (overall charge), promotional offer, availability of customer service center, value added service and speed are most important factors influencing customer satisfaction.
Keywords: customer satisfaction; 3G; mobile phone; services